A Comprehensive Guide to Core Needle Biopsies of the Breast - Shin, Sandra J.; Chen, Yunn-Yi.; Ginter, Paula S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Breast cancer remains the leading cause of cancer in women, which makes accurate diagnoses on core needle biopsy (CNB) specimens of vital importance in staging and guiding therapy decisions for patients. The first edition of this multi-authored text written by leaders in the field from major academic medical centers provided a comprehensive guide on diagnostic breast pathology in the core biopsy setting. In addition to in-depth coverage of benign and malignant entities encountered in breast core biopsies, the book provided additional resources to improve diagnostic accuracy such as pattern-based approaches to evaluation, mimickers of breast lesions arising in extra-mammary sites, and pitfalls specific to small tissue samples. In recent years, there have been several notable developments in the field of breast pathology including revisions in AJCC breast cancer staging, updated guidelines in the testing and reporting of ER, PR, and HER2, as well as implementation of immunotherapy and companion biomarker testing. In addition, several key updates were included in the most recent edition of the WHO Classification of Breast Tumours (2020). In addition to updates specific to individual breast entities, the second edition provides updates regarding biomarker testing in the primary and metastatic setting, and incorporates newly defined entities and updated definitions of rare tumors in alignment with the WHO Classification of Breast Tumours (2020). Furthermore, this edition addresses the role of CNB in companion biomarker testing for eligibility for immunotherapy in the context of advanced triple-negative breast carcinoma. Written by leaders in the field and edited by expert breast pathologists, The Second Edition of Comprehensive Guide to Core Needle Biopsies of the Breast is the definitive reference on breast core needle biopsies for practicing pathologists, pathology trainees, oncologists and clinicians of patients with breast disease. .
Essential Components of a Successful Breast Core Needle Biopsy Program: Imaging Modalities, Sampling Techniques, Specimen Processing, Radiologic/Pathologic Correlation, and Appropriate Follow-Up -- Pattern-Based Evaluation of Breast Core Needle Biopsies -- Multiples in Core Biopsy Samples -- Inflammatory, Reactive, and Infectious Conditions of the Breast -- Adenosis, Sclerosing Lesions, Microglandular Adenosis, and Mucocele-Like Lesions -- Papillary Tumors and Epithelial and Myoepithelial tumors (Pleomorphic adenoma, Adenomyoepithelioma, Malignant Adenomyoepithelioma) -- Fibroepithelial Lesions -- Columnar Cell Lesions -- Intraductal Proliferations (UDH, ADH, DCIS) -- Invasive Ductal Carcinoma, NST (including microinvasive carcinoma), Tubular Carcinoma, and Cribriform Carcinoma -- Triple-Negative/Basal-Like Breast Carcinomas -- Less Common Triple-Negative Breast Cancers and Salivary Gland-Type Tumors (Carcinoma with Apocrine differentiation, Metaplastic carcinoma, Adenoid Cystic Carcinoma, Secretory Carcinoma, Acinic Cell Carcinoma, Mucoepidermoid carcinoma, Tall Cell Carcinoma with Reversed Polarity) -- Special Histologic Types and Special Morphologic Patterns of Invasive Ductal Carcinoma, NST (Mucinous, Micropapillary, Mucinous Cystadenocarcinoma, Cystic Hypersecretory, Glycogen-Rich Clear Cell, Carcinoma with Osteoclast-Like Giant Cells, Neuroendocrine Neoplasms) -- Atypical Lobular Hyperplasia and Lobular Carcinoma In Situ -- Invasive Lobular Carcinoma -- Benign and Malignant Mesenchymal Tumors -- Vascular Lesions of the Breast -- Breast Tumors in Adolescents/Children and Males -- Lesions of the Nippe -- Lymphoid and Hematopoietic Tumors of the Breast -- Special Clinical Settings: Tumors Arising in Pregnancy, Pregnancy-Like (Pseudolactational) Proliferations, Breast Carcinoma in the Pre-neoadjuvant Chemotherapy Setting, Recurrent Breast Carcinoma, and Inflammatory Breast Carcinoma -- Current Standard Clinical Predictive Markers -- Future Role of Molecular Profiling in Small Breast Samples and Personalized Medicine -- Metastases to the Breast -- Dermatologic Mimickers of Breast Lesions Arising in the Breast Skin, Subcutis, or Axilla.
Keywords: Oncology; Pathology; Oncology; Radiology; Breast -- Needle biopsy; Breast -- Diseases -- Diagnosis; Medical laboratories